2021
DOI: 10.1186/s12974-021-02313-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of macrophage polarization on the expression of the oxytocin signalling system in enteric neurons

Abstract: Background The aim of the current study was to investigate the effect of macrophage polarization on the expression of oxytocin (OT) and the oxytocin receptor (OTR) in enteric neurons. Methods In this study, we used a classic colitis model and D-mannose model to observe the correlation between macrophage polarization and OT signalling system. In order to further demonstrate the effect of macrophages, we examined the expression of OT signalling syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…OT signaling system are important pathways to prevent free radical damage cascade and alleviate colitis. In vitro, macrophages polarized into M1 type by LPS contained pro‐inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α) in the supernatant of macrophages (Shi et al, 2021). Under the stimulation of IL‐4, MMs secretes anti‐inflammatory factors, which activate Smad2/3 pathway and upregulate OT signaling system by inhibiting the expression of PEG3 in intestinal neurons (Shi et al, 2021).…”
Section: Intestinal Neurons Regulate Intestinal Muscular Macrophages ...mentioning
confidence: 99%
See 1 more Smart Citation
“…OT signaling system are important pathways to prevent free radical damage cascade and alleviate colitis. In vitro, macrophages polarized into M1 type by LPS contained pro‐inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α) in the supernatant of macrophages (Shi et al, 2021). Under the stimulation of IL‐4, MMs secretes anti‐inflammatory factors, which activate Smad2/3 pathway and upregulate OT signaling system by inhibiting the expression of PEG3 in intestinal neurons (Shi et al, 2021).…”
Section: Intestinal Neurons Regulate Intestinal Muscular Macrophages ...mentioning
confidence: 99%
“…In vitro, macrophages polarized into M1 type by LPS contained pro‐inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α) in the supernatant of macrophages (Shi et al, 2021). Under the stimulation of IL‐4, MMs secretes anti‐inflammatory factors, which activate Smad2/3 pathway and upregulate OT signaling system by inhibiting the expression of PEG3 in intestinal neurons (Shi et al, 2021). Thus, it can be concluded that the OT signaling system is likely to be the signaling molecule for the dialogue between intestinal macrophages and neurons, and the modulation of the MMs phenotype may be critical in determining homeostasis or disease propensity.…”
Section: Intestinal Neurons Regulate Intestinal Muscular Macrophages ...mentioning
confidence: 99%
“…This has been shown in cell cultures of ENs, and the interaction is made possible via the STAT3 or NF-κΒ pathways. On the other side, anti-inflammatory MMs cause upregulation of oxytocin and its receptor via a TGF-β related mechanism [32]. Interestingly, lower concentrations of oxytocin and Muscularis Macrophages in Healthy and Diseased Gut DOI: http://dx.doi.org/10.5772/intechopen.109889 its receptor have been associated with more pro-inflammatory cytokines in mouse models of dextran sulfate sodium (DSS) associated colitis [33].…”
Section: Intrinsic Innervation and Mmsmentioning
confidence: 99%
“…In vitro , after macrophages were polarized to M1 type by LPS, pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) contained in macrophage supernatants inhibited the expression of OT and OTR in intestinal neurons; after macrophages were polarized to M2 type by IL4, anti-inflammatory cytokines (TGF-β) contained in macrophage supernatants promoted OT and OTR in intestinal neuronal expression. Therefore, it has been suggested that macrophages are polarized to M1 type during the inflammatory phase and to M2 type during the recovery process ( 84 ).…”
Section: Regulation Of Intestinal Immune Cells On Nerve Cellsmentioning
confidence: 99%